Power reconfigurations and enterprise development: Elite contestations and business groups in Pakistan / Ayesha Shoukat - Ayesha, Shoukat (2016)
Rapid reconfigurations of power following regime shifts have contributed to the rise and fall of major business groups in Pakistan. The ascendance and decline of Pakistan’s leading enterprises is due to constantly changing collusions and contestations between power elites in institutions such as the military, political parties, bureaucracy, religious groups and international agencies as well as landlords who play a vital role in crafting each regime. This study analyzes how corporate elites deal with each other as well as with other power elites when a regime change occurs, leading to the making of a government headed by a military dictator or a democratically elected Prime Minister. On the basis of detailed historical political and financial analyses of the performance of business groups, this study provides insights into the outcomes of persistent regime change on corporate development in Pakistan. The theoretical gap in the literature that is covered in this study is the impact of reconfigurations of power among elites on corporate ownership patterns in a developing economy. The theoretical ideas employed here have benefited from Porta’s assessment of state-business nexuses and their implications on corporate ownership and control patterns as well as Faccio’s theorizing of political-business connections. A qualitative analysis is provided of key historical events that offer insights into the role and contribution of each elite group under different regimes that have held power in Pakistan. In-depth case studies of Pakistan’s leading enterprises are provided in this study. Complementing these case studies are quantitative financial and statistical analyses of the performance of publicly-listed companies of these business groups. This research provides extensive data in the form of the change in the financial performance that occurred among business groups following their creation of political connections with elites in control of the state. This mode of analysis helps identify the business groups favored by each regime, through the state’s ability to deploy bank loans as well as economic rents to key corporate figures. This study indicates that while all power elites are strong enough to build and sustain their presence in society, the military elite is the only one that has worked systematically and institutionally to sustain its hegemonic position. Corporate elites use different networking techniques to develop links with ruling elites. The position of business groups in the corporate world keeps shifting with each regime change on the basis of the personal contacts businesspeople have with elites in control of the state. The ‘new rich’ are those business groups that focused on the services sector and real estate. The industrial sector is still controlled by the old business groups. The corporate sector is highly responsive to political decisions and the outcomes of contestations between different power elites. Despite political, security and economic shocks, the corporate sector has experienced massive expansion since 2002 and its sustainability after 2007 has been facilitated by the democratic governments that were able to complete their tenure.